CLASSES OF ARRAYS WITH INDEX NON-OVERLAPPING COMPONENTS AND METHODS OF THEIR FORMING - I. P. Kadiev; P. A. Kadiev (Вестник Дагестанского государственного технического университета: Технические науки)
The concept of crossing or non-crossing sets with objects of different nature. The principles, which give the transformed arrays properties that increase the efficiency of information technology. As the main characteristic defining the relationship on the sets, forming the arrays, we consider the system of indexing of elements of the compared sets. The terms an index of non-crossing array components are. We propose a new class of arrays which components are indexed by disjoint sets, the notion of « non-crossing index sets»; provides methods of forming arrays of different classes. It is proved that any permutation of the elements of arrays are implemented with some regularity, associated with changes in indexing. The developed method of formation of arrays based on cyclic shifts of the rows and columns of the original array for the proposed algorithms. The task of forming arrays with disjoint sets of three types has been solved. The paper analizez the proposed options for building arrays with disjoint components - sets, proving that the properties of non-crossing components are stored for the first type arrays in all permutations of columns.